The Function of Heat Shock Transcription Factors in Sex Differentiation in Cynoglossus semilaevis - Zhijie Li; Xuexue Sun; Haipeng Yan; Lijun Wang; Xihong Li; Na Wang; Min Wei; Wenteng Xu (Animals)
Chinese tongue sole (Cynoglossus semilaevis) is an important marine fish in China. It has sexual dimorphism. The weight and growth rate of female fish are much greater than those of male fish. However, high temperatures can induce sex reversal in genetic female fish (ZW) to phenotypic male fish; thus, identifying the genetic elements involved in temperature perception will provide the molecular basis for sex control. The heat shock transcription factor (hsf) is known as an important component of temperature sensing and mediates the heat shock response in fish such as Danio rerio; however, its function in C. semilaevis is unclear. In this study, five hsf genes (hsf1, hsf2, hsf4, hsf5a, and hsf5b) were identified in tongue sole and found to be expressed in the gonads at different developmental stages, peaking from 7M to 1Y. Gonadal in situ hybridization revealed that hsf gene signals were mainly localized in germ cells, e.g., sperm in the testis and all-stage oocytes in the ovary. Upon high-temperature stimulation, the expression of the hsf gene in the gonads increased gradually with increasing stimulation time, but different hsf genes presented different response patterns. After the RNA interference of hsf in the testis and ovarian cell lines, a series of sex-related genes, such as foxl2 and dmrt1, significantly changed. In vivo RNA interference had an effect on the female gonads and mainly affected neurl3 expression. On the basis of these data, we speculate that hsf responds to temperature stimulation and plays an important role in sex differentiation. This study helps elucidate the relationship between temperature sensing and sex differentiation in C. semilaevis.